2022
DOI: 10.2337/dc21-2521
|View full text |Cite
|
Sign up to set email alerts
|

Association of Longitudinal Trajectories of Insulin Resistance With Adverse Renal Outcomes

Abstract: OBJECTIVE To analyze the relationship between time-serial changes in insulin resistance and renal outcomes. RESEARCH DESIGN AND METHODS A prospective cohort of subjects from the general population without chronic kidney disease (CKD) underwent a biennial checkup for 12 years (n = 5,347). The 12-year duration was divided into a 6-year exposure period, where distinct HOMA for insulin resistance (HOMA-IR) trajectories were ident… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The relationship between IR and CKD had been demonstrated in previous studies (7)(8)(9)12). Irrespective of diabetes prevalence, a rising trend in HOMA-IR was related to an increased risk of unfavorable renal outcomes during the course of a 12-year prospective cohort study of the general population without CKD (hazard ratio = 2.06, 95% CI: 1.62-2.60, P < 0.001) (7).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The relationship between IR and CKD had been demonstrated in previous studies (7)(8)(9)12). Irrespective of diabetes prevalence, a rising trend in HOMA-IR was related to an increased risk of unfavorable renal outcomes during the course of a 12-year prospective cohort study of the general population without CKD (hazard ratio = 2.06, 95% CI: 1.62-2.60, P < 0.001) (7).…”
Section: Discussionsupporting
confidence: 55%
“…Insulin resistance (IR) is a state of diminished response to insulin in target cells and an important pathogenic mechanism for the development of metabolic diseases. It is present in many chronic diseases, including diabetes, cardiovascular disease, hypertension, and CKD (6,7). Furthermore, several investigations revealed that being overweight and having metabolic syndrome (MS) was significantly linked to a moderate decline in eGFR (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, muscle mass is inversely related to insulin resistance and metabolic syndrome severity 46 . A 12-year longitudinal cohort study revealed that increasing insulin resistance over time was consistently associated with a heightened risk of adverse renal outcomes, irrespective of diabetes prevalence 47 . Chronic renal insu ciency often leads to muscle wasting, which may be worsened by low-protein diets aimed at delaying disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…First, IR is associated with an increased risk of metabolic diseases, such as hypertension, abnormal glucose metabolism, hyperuricemia, and dyslipidemia ( 19 , 20 ), which are also risk factors for CKD ( 21 ). Second, animal and human studies demonstrated that hyper-insulinemia increases sodium reabsorption, induces glomerular hyperfiltration, which increases renal injury ( 22 24 ).…”
Section: Discussionmentioning
confidence: 99%